Curcumin-Cellulose Film for Visual Detection of Fish Spoilage - Risna Erni Yati Adu; Gebhardus Djugian Gelyaman (Jurnal Sains dan Terapan Kimia, 2024)
Fish spoilage can be monitored visually through a responsive film to freshness and pH changes. This study aims to produce a film that is responsive to pH changes in the fish environment from curcumin, a safer natural dye. The chemical, physical, and functional characteristics as well as the film response to pH change and fish freshness during storage were studied here. Cellulose-curcumin films were fabricated by impregnation of curcumin into cellulose films. The chemical characteristics such as functional groups and surface morphology were determined by FT-IR and SEM respectively. FT-IR presents an interaction between curcumin and cellulosic polymer. The impregnation of curcumin into the cellulose film caused the segregation on the film surface observed on the SEM photos and decreased the swelling index. Cellulose-curcumin films are highly responsive to both acidic and alkaline pH. At an acidic pH, the film is yellow while at an alkaline pH the film changes to a red-brown color. The film also presented a highly color change from orange to reddish brown with increasing of fish storage days. A higher antioxidant activity of 5.54% was presented by curcumin film than the cellulose pure film. Therefore, cellulose-curcumin film can be used to detect fish spoilage through direct visual inspection.